2019
DOI: 10.1371/journal.pone.0223489
|View full text |Cite|
|
Sign up to set email alerts
|

Frozen by stress: Stress increases scope insensitivity

Abstract: Stress has become a widely experienced state all around the world, and previous literature has found that stress impacts individuals’ cognition, emotion, coping behaviors and psychological well-being in general. Relatively little is known about how stress influences individuals’ perception of stimuli changes, a ubiquitous phenomenon known as scope sensitivity. In the current work, we explore whether individuals with higher levels of chronic stress are sensitive to stimuli changes, such as price and quantity di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Under stressed circumstances, employees are not able to meet the project schedule, budget and scope (the definition of project efficiency) (Serrador and Turner, 2015), because increased stress negatively affects employees' focus on performing project tasks (Khosravi et al, 2020). Moreover, according to Al-Janabi et al (2020), job stress results in re-work (associated with additional costs and time), since stress impacts individuals' cognition, sensations, coping behaviors and psychological well-being in general (Li et al, 2019). According to Xie and Johns (1995), job stress is negatively associated with the scope of a job (project scope in this case).…”
Section: Job Stress As a Mediator Between Despotic Leadership And Pro...mentioning
confidence: 99%
“…Under stressed circumstances, employees are not able to meet the project schedule, budget and scope (the definition of project efficiency) (Serrador and Turner, 2015), because increased stress negatively affects employees' focus on performing project tasks (Khosravi et al, 2020). Moreover, according to Al-Janabi et al (2020), job stress results in re-work (associated with additional costs and time), since stress impacts individuals' cognition, sensations, coping behaviors and psychological well-being in general (Li et al, 2019). According to Xie and Johns (1995), job stress is negatively associated with the scope of a job (project scope in this case).…”
Section: Job Stress As a Mediator Between Despotic Leadership And Pro...mentioning
confidence: 99%
“…According to a nationwide study by the American Psychological Association (APA) in 2020 [18], more than 60% of surveyed Americans reported experiencing high stress. Scholars have defined stress as a psychological state experienced by people confronted with demanding, challenging, and threatening events or situations, also termed stressors [19,20]. Research has shown that stressors can be either incidental challenging events or chronic threatening situations [20,21].…”
Section: Research About Stressmentioning
confidence: 99%
“…Scholars have defined stress as a psychological state experienced by people confronted with demanding, challenging, and threatening events or situations, also termed stressors [19,20]. Research has shown that stressors can be either incidental challenging events or chronic threatening situations [20,21]. For example, major life events such as college entrance examinations or divorce, and environmental factors including natural disasters or air pollution, serve as stressors that contribute to stressful feelings [21][22][23].…”
Section: Research About Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…As we age we experience changes in our hair and scalp health, these changes are multifactorial with contributions from genetic predisposition, pathological states, stress, pharmacotherapy, and nutritional inadequacies [2]. Over the generations there has been a rapid increase in stress due to various factors and generations such as millennials and Generation Z are more increasingly living under stress [3]. This stress has the potential to alter the immune response and transiently hamper hair growth [4].…”
Section: Introductionmentioning
confidence: 99%